(untitled) (Theological Kronos, 2018)
This thesis departs from the reading and analysis of the text of Lucas from lasat Jesus’ dinner ith your disciples before facing the death for crucifixion, in the context of the Easter Jewish dinner. It realizes the reading and and analysis of Lucas’s Biblical text, and checks yes Jesus’ invitation another different pretensión would not have that her (it) of perpetuating a liturgical act about your “death that gives salvation”. For this presents the analysis of the Biblical - theological category of “memory” and from there it considers a re-reading of the text, for there illuminating the pastoral work about the topic of the victims in Colombia. “It” is not a question of “dismantling” an acto or liturgical rite but to giving a renewed sense in the light of this category; which leads, Little by Little, to the consideration of the topic of the victim, in the first term of Jesus himself and also of all other victims who have traversed a similar luck in our current context. In conclusion the examination of the category “memory” throws a renewed accent forthwith liturgical of the dinner of the Gentleman from Jesus’consideration as victim of a social, political and religious adverse system and of the importance of the above mentioned category in the search of the justice “anamnética” for the victims of the conflicto in our country.